2017
DOI: 10.1002/2017gl074276
|View full text |Cite
|
Sign up to set email alerts
|

MESSENGER observations of the energization and heating of protons in the near‐Mercury magnetotail

Abstract: The energization and heating processes for protons in the near‐Mercury tail are examined with MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) observations. In a case study, suprathermal proton particle flux (STPF) and proton temperature are observed to be clearly enhanced during near‐Mercury substorm dipolarizations, indicating the proton energization and heating processes. STPF and proton temperature distributions in near‐Mercury central plasma sheets display dawn‐dusk asymmetries, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 46 publications
4
54
0
Order By: Relevance
“…The protons around the dipolarization front are moving duskward in the current sheet (see the proton streamlines in Figure ). However, the high‐speed proton jets are more frequently observed in the dawn sector near Mercury, which is consistent with MESSENGER observations (Sun et al, ). Since both the dipolarization fronts and the high‐speed protons prefer the dawnside, it is possible that the protons are accelerated by the dipolarization fronts (Zhou et al, ).…”
Section: Simulation Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The protons around the dipolarization front are moving duskward in the current sheet (see the proton streamlines in Figure ). However, the high‐speed proton jets are more frequently observed in the dawn sector near Mercury, which is consistent with MESSENGER observations (Sun et al, ). Since both the dipolarization fronts and the high‐speed protons prefer the dawnside, it is possible that the protons are accelerated by the dipolarization fronts (Zhou et al, ).…”
Section: Simulation Resultssupporting
confidence: 90%
“…In previous studies at Mercury, Sun et al () has shown clear dawn‐dusk asymmetry of dipolarization fronts in the near‐Mercury‐neutral‐line region with more dipolarization fronts on the dawnside plasma sheet than on the duskside plasma sheet. The following studies on the dipolarization fronts in the near‐Mercury plasma sheet, proton energization and heating, energetic electrons and proton bulk flows have shown the similar dawn‐dusk asymmetries (Dewey et al, , ; Sun et al, ).…”
Section: Messenger Observations In the Nightside Plasma Sheetmentioning
confidence: 96%
See 1 more Smart Citation
“…Solar wind and planetary ions in Mercury's PS are known to have large gyroradius relative to the scale length of magnetic field variations due to Mercury's weak intrinsic magnetic field. At Mercury, particles were also observed to be energized and accelerated near the X-line by magnetic reconnection and reconnection-related phenomena, such as dipolarization fronts (Dewey et al, 2017;Sun et al, 2017). At Mercury, particles were also observed to be energized and accelerated near the X-line by magnetic reconnection and reconnection-related phenomena, such as dipolarization fronts (Dewey et al, 2017;Sun et al, 2017).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Particles energized and accelerated by magnetic reconnection and dipolarization fronts (Sun et al, 2017) execute a larger, more chaotic gyromotion and are more likely to be lost from the flux tubes into other magnetospheric regions or shadowing of the nightside magnetopause. During active magnetic reconnection, particle scattering effects play an even more important role in the transport of particles from one magnetospheric region to another.…”
Section: Summary and Discussionmentioning
confidence: 99%